Digital research on the resilience control of water ecological space under the concept of urban-water coupling - Yang, Hua; Ning, Qimeng; Zhou, Hui; Lai, Nan; Song, Qidi; Ji, Qianfu; Zeng, Zhiwei (Frontiers in Environmental Science, 2023)
The construction of digital governance of national land space depends greatly on the development of a digital model for robust control of water and ecological space. However, how changes to the urban-water coupling relationships affect the resilience control of water ecological space is rarely reported. The evolution characteristics of urban and water space in the study area from 2000 to 2020 and the correlation between them are analyzed based on the grid analysis using InVEST and Moran’I methods. Based on the theory of human-environment interaction territorial system to provide a theoretical framework to explain the urban and water space. We used digital to construct an resilience control framework in the Dongting Lake area based on the correlation between the urban and water space.The results show that: (1) From 2000 to 2020, the geographical evolution of towns and cities in the research area displayed obvious spatial variation in intensity, indicating a process of expansion and change. The regional and temporal fluctuations of the water conservation function are significant. The mountainous areas in the east, south, and northwest are where the high values of the water conservation function are primarily found. These regions have more vegetation, which increases the water conservation function. (2)According to the results of local binary spatial autocorrelation analysis, it can be seen that from 2000 to 2020, the high-high agglomeration of town space and water-related is mainly distributed in Linxiang City, Yueyang County, Miluo City, Li County, and Yiyang City, and the low-low agglomeration is mainly distributed in Dongting Lake, Datong Lake,and along the Yangtze River. (3)Based on how urban spatial evolution affects water ecological space, we construct a theoretical framework of urban-water coupling and establish a digital model of water ecological space resilience control in the Dongting Lake area from four perspectives: threshold, visualization, dynamics, and intelligence.